A New Unified Integral Formula Involving the Function and General Multivariable Polynomials - Ndiritu, Sharon Anne (Journal of Research in Vocational Education, 2026)
functions. The outcomes of this research are expected to generalize and unify various known results, while also offering new mathematical tools for application in fields such as mathematical physics, engineering, and computational analysis.